Efektivitas Konseling Kelompok Rational Emotive Behavior Therapy dalam Meningkatkan Regulasi Emosi Remaja Sekolah Menengah Atas - Sari, Putri Mayang; Lubis, Saiful Akhyar; Daulay, Nurussakinah (Universitas Muhammadiyah Metro, 2023)
Low emotional regulation abilities indicate that students cannot control the emotions they feel and cannot control the emotions they will display. This research aims to determine the effectiveness of Rational Emotive Behavior Therapy (REBT) group counseling in improving students' emotional regulation abilities. This research uses a Quasi-Experimental type with a non-equivalent control group design. In the two groups, both pretests and posttests were carried out. The research subjects were class IX students of SMAN 1 Hamparan Perak who were identified as having low emotional regulation abilities. As for the results of the Wilcoxon Signed Rank Test calculation, the Z value obtained is -2.805 with a p-value (Asymp. Sig 2 tailed) of 0.005, which is less than the research critical limit of 0.05, so the hypothesis decision is to accept H1 or which means there is a difference significant between the pretest and posttest groups. Apart from that, the average posttest score in the experimental class was more significant than that of the control class (100.6> 71). It can also be seen from the percentage level in the high category. Namely, the experimental class is higher than the control class (10% > 0%). Based on the results of this research, it can be concluded that the Rational Emotive Behavior Therapy technique can improve the emotional regulation abilities of the class.